Impact of worldwide lockdown during Pandemic on micro and small Enterprises (special on World Handicraft sector): a study on determinants and exit strategies for promotion of Global handicraft sector - Uma shankar yadav Yadav; mano ashish Tripathi; susmita tripathi (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Between 2020 to mid-2022,the world economy was severely affected by the COVID-19 pandemic. Maintaining operations during a global crisis was extremely difficult for small and medium enterprises, especially in handicraft sectors. Entrepreneurs who do not have crisis management strategies in place, risk having their businesses shut down unexpectedly. Hence, the researchers aimed to understand and analyze the determinants of microenterprises (Handicraft sector) shutdown and exit strategies during the pandemic. This study utilized a descriptive research design, and registered microenterprises in India were purposively selected in the areas of Cavite. The findings of the study revealed that the majority of the microenterprises were sole proprietors that had been in operation for 2 to 5 years and had a capitalization of less than INR 500,000.00. Consequently, the respondents' most common problems in managing the enterprise were limitations on direct marketing which also involved bill payments, adoption of the online platform, and work-from-home setup. Most of the determinants of problems that led to business failure during the pandemic were obstacles in the realignment of their respective goals owing to the pandemic, their ability to pay operational expenses, difficulties in product innovation, and their failure to react to the changes in the business environment. Exit strategies used by microenterprises included declaring bankruptcy, refinancing, and selling the business to family or friends. Finally, the researchers recommended crisis-sensitive interventions among the small industries (Handicraft sector) entrepreneurs which involve national government provisions of financial safety nets, retooling, and training of pandemic-sensitive enterprise strategies for micro-entrepreneurs, especially in the handicraft sector and also study the impact of lockdown on MSME.